Panthera tigris altaica (Carnivora, Felidae) in the Lazovsky State Nature Reserve and in the adjacent non-protected area (Far East of Russia) - Galina P. Salkina; Nadezhda Ya. Poddubnaya; Vladimir S. Kolesnikov; Vera A. Nikandrova (Nature Conservation Research: Заповедная наука, 2022)
To assess the state of the Panthera tigris altaica (hereinafter – tiger) population, its annual monitoring is being carried out on 16 sites within its range, as this subspecies is still considered threatened. These sites include state nature reserves and adjacent territories, which differ in their protection status. In this paper, a number of tiger individuals in groups and reproduction have been compared on these sites to identify factors that determine these parameters. The tiger population in the Lazovsky State Nature Reserve (area of 1210 km2) was compared with the tiger population in an unprotected area (area of 988 km2), which, similarly to the Protected Area, is located on the coast of the Sea of Japan. A description and comparison of these two sites is given. The study has been carried out in 1997–2021 in the Lazovsky State Nature Reserve, and in 1997–2012 in the unprotected site «Lazovsky District». During the winter, information was collected about tiger tracks in the study area, and data on predator tracks were collected out on stationary routes during two field counts. In the Lazovsky State Nature Reserve, the density of routes in various years was 1.0–1.5 km per 10 km2, 1.2 km per 10 km2 in the site «Lazovsky District». Tiger individuals were identified by the width of paw prints. Tracks differed by more than 2 cm were considered belonging to different individuals. Indicators of the tiger population was about twice higher in the Lazovsky State Nature Reserve than in the unprotected site «Lazovsky District». In 1997–2012, in both Lazovsky State Nature Reserve and unprotected site «Lazovsky District», the population density of both adult and subadult tigers was respectively 8.6 ± 0.7 individuals per 1000 km2 and 5.3 ± 0.5 individuals per 1000 km2, while this parameter was respectively 3.1 ± 1.0 individuals per 1000 km2 and 1.7 ± 0.04 individuals per 1000 km2 for tiger cubs younger than a year. The tiger track density in the Lazovsky State Nature Reserve was 3.03 ± 0.51 tracks per 100 km, taking into account the time passed after the snowfalls covering all tracks; on the site «Lazovsky District», this indicator was 1.33 ± 0.27 tracks per 100 km. In 1997–2012, the population density of adults and subadults was significantly (F = 59.40, p < 0.001) higher in the Lazovsky State Nature Reserve than on the site «Lazovsky District». The population density of tiger cubs (F = 6.30, p < 0.018) and the track density (F = 4.86, p < 0.036) were also significantly higher in the Protected Area than in the unprotected one. The survival rate of tiger cubs was also higher in the Lazovsky State Nature Reserve. Here, the proportion of tiger litters with one cub was 16% (n = 4), with two cubs 48% (n = 12), with three 32% (n = 8), and with four 4% (n = 1) of the total number. On the unprotected site «Lazovsky District», the proportion of litters with one cub was 53% (n = 8), with two 27% (n = 4), and with three 20% (n = 3) of the total number. A downward trend in the population density of tiger cubs was found on the site «Lazovsky District». In 2012–2021 in the Lazovsky State Nature Reserve, the average population density was 8.9 ± 1.8 individuals per 1000 km2 for adult and subadult tigers, and 4.3 ± 1.1 individuals per 1000 km2 for tiger cubs, while the average tiger track density was 2.39 ± 0.68 tracks per 100 km. During this period, the population density of tiger cubs decreased in the Protected Area, and there was also a tendency towards a decrease in the relative number of adults and subadults. The regular three-year cycle in the dynamics of the tiger track density in the Lazovsky State Nature Reserve indicates that environmental factors predominantly influence tiger groups here. No regular cycle was observed on the unprotected site «Lazovsky District». This finding and the lower number of tiger individuals in this area are associated with the negative impact of related anthropogenic factors, namely poaching, hunting, and logging. Recreational pressure also affects the tiger groups. In the last decade, the tiger group in the Lazovsky State Nature Reserve has been exposed to anthropogenic factors from the adjacent area. It is concluded that the further protection of the tiger and the increase in its number is possible if Protected Areas of various statuses are established, if extensive buffer zones are created around new and existing Protected Areas, if hunting is prohibited and logging is limited. The use of agricultural lands for other purposes around Protected Areas should be forbidden.